Результати корекції рогівкового астигматизму при факоемульсифікації катаракти з імплантацією торичної інтраокулярної лінзи та за програмою "Біоптика" - Завгородня, Наталія Григорівна; Новікова, Валерія Юріївна; Zavgorodnya, N. G.; Novikova, V. Yu. (My University, 2018)
Для оцінки ефективності хiрургiчного лiкування катаракти на очах із рогівковим астигматизмом при факоемульсифікації катаракти з iмплантацiєю торичної інтраокулярної лінзи (ІОЛ) та за методом «Біоптика» обстежений 31 хворий (42 ока). Виявлено, що імплантацiя торичних ІОЛ, як i використання програми «Бiоптика», дозволяє досягти високої гостроти зору на очах з астигматизмом. Вірогідне зменшення загального астигматизму мало місце в усіх хворих; вiддаленi результати бiльш стабiльнi при застосуваннi програми «Бiоптика». Background. One of the most urgent tasks in modern cataract surgery is to obtain the most predictable and accurate refractive result. At the present stage, one of the proposed methods for astigmatism correction is the use of toric intraocular lenses (IOLs). To correct these refractive disorders, various methods of refractive surgery are proposed. The purpose was to evaluate the effectiveness of surgical treatment of cataract in the eyes with corneal astigmatism during phacoemulsification of cataract with implantation of toric IOL and using the Bioptics method. Materials and methods. We have examined 31 patients (42 eyes) aged 20 to 79 years with cataract and corneal astigmatism from 0.5 to 3.75 D according to keratometry, operated for cataract. Besides the general ophthalmological examination, all patients were examined with A-scan, endothelial microscopy, optical biometry, calculation of toric IOL. Patients in the first group (n = 17; 22 eyes) underwent cataract phacoemulsification and implantation of toric IOL. The second group consisted of 14 patients (20 eyes) operated using the Bioptics method. Results. Results showed a significant increase in visual acuity as a result of surgical treatment in all patients. Also, the astigmatism according to autorefractometry after the operation was at the level of 0.58 ± 0.06 D, in contrast to the baseline — 2.61 ± 0.39 D, which indicates a decrease in astigmatism in group І by 77.7 % (p < 0.01) and a decrease by 75 % (p < 0.01) in group II (before — 2.80 ± 0.37 D and after — 0.70 ± 0.15 D). The index of total astigmatism in patients who were implanted with toric IOL increased for a year by 15.9 %, from 0.58 ± 0.06 D to 0.69 ± 0.18 D, and in the second group — by only 2.8 % (from 0.70 ± 0.15 D to 0.72 ± 0.14 D). Conclusions. Phacoemulsification of cataract with the implantation of toric IOL, as well as use of the Bioptics program allows achieving high visual acuity in the eyes with concomitant corneal astigmatism. Reduction of total astigmatism is achieved in all operated patients. The remote refractive results of astigmatism correction are more stable when using the Bioptics program. It is necessary to monitor the more distant results of refractive indexes in these patients and to develop the ways to improve the surgical treatment of cataract in the eyes with corneal astigmatism.
Results of corneal astigmatism correction in phacoemulsification of cataract with the implantation of toric intraocular lenses and using the Bioptics program
Keywords: торичні ІОЛ; «Біоптика»; корекція астигматизму; toric intraocular lenses; Bioptics; astigmatism correction